High specific surface area N-doped activated carbon from hydrothermal carbonization of shaddock peel for the removal of norfloxacin from aqueous solution - Niu, Xinyong (Water science and technology : a journal of the International Association on Water Pollution Research, 2022)
A novel N-doped activated carbon (NAC) derived from shaddock peel was investigated to remove norfloxacin (NFX) from aqueous solution. The Box-Behnken central composite design (BBD) was used to optimize the preparation conditions of NAC. The specific surface area of NAC was 2,481.81 m2 g-1, which was obtained at 1,106 K activation temperature, 2.4 h residence time, and 2.3:1 mass ratio of KOH to hydrochar. Moreover, the equilibrium data were perfectly represented by Langmuir and Koble-Corrigan isotherms, and the adsorption process was precisely described by the pseudo-second-order kinetic model. Besides, the adsorption of NFX on NAC was mainly controlled by π-π electron-donor-acceptor (EDA) interaction, hydrophobic effect, hydrogen-bonding, electrostatic interaction and Lewis acid-base effect. The maximum monolayer adsorption capacity of NFX was 746.29 mg g-1 at 298 K, implying that NAC was a promising adsorbent for the removal of NFX from aqueous solution